Satus Kutus Nyuh Madan in the Balinese Usada Tradition - I Ketut Dharma Kresna Wijaya; I Wayan Suka Yasa; I Gusti Bagus Wirawan (International Journal of Interreligious and Intercultural Studies, 2025)
Usada Bali is a traditional healing system rich in empirical and spiritual knowledge, transmitted through palm-leaf manuscripts (lontar), cultural practice, and Balinese Hindu cosmology. This study explores the functions, classifications, and processing of Nyuh Madan (Cocos nucifera) as a sacred medicinal plant within the usada tradition. The research investigates its use as a herbal remedy, a medium for spiritual purification, a tool in ritual healing, and a cosmological symbol in Balinese belief systems. Employing a qualitative descriptive-analytic approach supported by structural-functional theory, Ayurvedic principles, and reception theory, data were gathered through participatory observation, in-depth interviews with balian (traditional healers) and pemangku (temple priests), as well as philological analysis of lontar texts. The findings reveal over 100 distinct types of Nyuh Madan, classified by morphology, spiritual properties, and therapeutic function. The traditional production of Virgin Coconut Oil (VCO) through natural fermentation and sedimentation preserves the bioactive integrity of the plant. Laboratory tests confirm that VCO contains high concentrations of lauric acid and antioxidants with antimicrobial, anti-inflammatory, and immune-stimulating properties. User testimonials further validate its effectiveness in treating both physical ailments (sekala) and metaphysical imbalances (niskala). These results affirm Nyuh Madan not merely as an agricultural commodity but as an intangible cultural heritage symbolizing the harmony of health, spirituality, and ecological wisdom in Balinese life